Policy Recommendations for Sustainable Development, Volume 2
VIII, 45 p. 19 illus., 18 illus. in color.
Keywords: The book contains policy-related publications based on research conducted by the National Institute of Advanced Studies. These publications address and support sustainable development goals, such as energy and the environment, education, inequality, human development, and peace research, among others. This volume fosters comprehensive research focused on these global targets and endeavors to address some of society's greatest grand challenges. The book will be extremely beneficial for researchers, academicians, practitioners, and policymakers working in the areas of the 17 Sustainable Development Goals (SDGs).